Secure Encryption by Combining Asymmetric and Symmetric Cryptographic Method for Data Collection WSN in smart Agricultur - AMETEPE, François; AHOUANDJINOU, SÈMÈVO ARNAUD ROLAND MARTIAL (My University, 2019)
The exponential outgrowth of wireless sensor networks and the Internet of Things with emerging of cheap applications are facilitating this age, when all things are becoming smarter, wireless and more connected. Designing a secure, a scalable, a robust, and a reliable WSN needs sufficient knowledge to overcome the inherited limitations of storage capacity, processing power, and communication range. According to [4], cryptographic techniques and key management tools to bring computational and space challenges to resource constraint hardware. In this paper, we design a secure service architecture for data transmission in an intelligent network for a crop monitoring in agriculture fields. The proposed cryptosystem using an hybrid approach by combining asymmetric and symmetric of cryptographic depending on architecture level The first experiments results obtained by using sensors such as ATMega, MSP and Raspberry range are very encouraging and support our idea.
Keywords: Wireless Sensor Network; Internet of Things; Advanced Encryption Standard; Elliptic Curve Cryptograph